Comparative environmental impact assessments of green food certified cucumber and conventional cucumber cultivation in China. Issue 5 (29th May 2017) - Wang, Fang; Liu, Yuexian; Ouyang, Xihui; Hao, Jianqiang; Yang, Xiaosong
Abstract: The need to ensure food safety has been recognized in China and the 'Green Food' system is used to restrict the use of chemical fertilizers and pesticides in its certified products. There has been limited study of the environmental impacts associated with the production of green food certified (GFC) products in China. In this study, life cycle assessment was used to evaluate environmental impacts of GFC cucumber cultivated under a greenhouse system in the suburbs of Beijing relative to conventional cultivation (CON), with the aim of identifying the key areas of potential environmental burden in cucumber cultivation. Eight environmental impact categories are considered, including global warming potential, energy depletion (ED), water depletion, acidification potential, aquatic eutrophication (AEU), human toxicity (HT), aquatic eco-toxicity (AET) and soil eco-toxicity (SET). Results showed that the environmental index of the GFC cucumber system was higher than that of the CON cucumber system. SET, EU and ED were identified as the main potential environmental impacts in cucumber systems, largely caused by fertilizer use on the farm. The potentials of HT and AET in GFC cucumber were lower than those in the CON system, mainly due to the reduced use of chemical pesticides. The agricultural input of plastics was the main contributor to energy depletion in both cucumber cultivation systems. Potential approaches to mitigate the environmental impacts of cucumber cultivation include increasing the fertilizer use efficiency, avoiding use of animal manure with high heavy metal content and recycling of plastics under the GFC cultivation system.